Neu-Laxova Syndrome Is a Heterogeneous Metabolic Disorder Caused by Defects in Enzymes of the L-Serine Biosynthesis Pathway - ELÇİOĞLU, HURİYE NURSEL (CELL PRESS, 2014)
Neu-Laxova syndrome (NLS) is a rare autosomal-recessive disorder characterized by a recognizable pattern of severe malformations leading to prenatal or early postnatal lethality. Homozygous mutations in PHGDH, a gene involved in the first and limiting step in L-serine biosynthesis, were recently identified as the cause of the disease in three families. By studying a cohort of 12 unrelated families affected by NLS, we provide evidence that NLS is genetically heterogeneous and can be caused by mutations in all three genes encoding enzymes of the L-serine biosynthesis pathway. Consistent with recently reported findings, we could identify PHGDH missense mutations in three unrelated families of our cohort. Furthermore, we mapped an overlapping homozygous chromosome 9 region containing PSAT1 in four consanguineous families. This gene encodes phosphoserine aminotransferase, the enzyme for the second step in L-serine biosynthesis. We identified six families with three different missense and frameshift PSAT1 mutations fully segregating with the disease. In another family, we discovered a homozygous frameshift mutation in PSPH, the gene encoding phosphoserine phosphatase, which catalyzes the last step of L-serine biosynthesis. Interestingly, all three identified genes have been previously implicated in serine-deficiency disorders, characterized by variable neurological manifestations. Our findings expand our understanding of NLS as a disorder of the L-serine biosynthesis pathway and suggest that NLS represents the severe end of serine-deficiency disorders, demonstrating that certain complex syndromes characterized by early lethality could indeed be the extreme end of the phenotypic spectrum of already known disorders.
Keywords: PHOSPHOSERINE AMINOTRANSFERASE; CANCER-CELLS; DEFICIENCY DISORDERS; MUTATIONS; GLYCINE; PROTEIN; PHGDH